(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to reveal The effect of Landa’s model on acquiring generative thinking skills for students of the Department of Art Education in producing design works In order to verify the objective of the research, the following null hypotheses were developed: There is no statistically significant difference at the level of statistical significance (0.05) between the mean scores of the experimental group students and the average scores of the students in the control group on the cognitive test before and after. To validate the hypotheses, where the research sample was selected from the University of Maysan / Department of Art Education / the third grade, which numbered (25) male and female students, and it was designed, presented to a group of experts, and presented to a group of experts. and specialists